The Namesake - Lahiri, Jhumpa (New York Mariner Books, 2004)
Thirty years in the life of Gogol Ganguli, born to Calcutta immigrants shortly after their 1960's arrival in Boston. Gogol's name is a constant burden to him, so he legally changes it to Nikhil. Yet, as a first-generation American stumbling along the path to maturity, he remains defined by the name Gogol. Some descriptions of sex and strong language.
Keywords: Children of immigrants -- East Indian Americans -- Young men